Determinants of Hypertension Treatment Adherence during the COVID-19 Pandemic: Lesson Learned from Various Studies Sites in Indonesia - Raehan Satya Deanasa; Alifa Alya Zalfa; Nurul Mufliha Patahuddin; Lathifah Dzakiyyah Zulfa; Sofia Hana; Anak Agung Bagus Putra Indrakusuma; Aizar Vesa Prasetyo; Gita Julianti Malik; Hesti Azzahra Tosadapotto; Raza Syahlevi Suwandri; Muhammad Nur Mahmudi; Rizma Adila Syakurah (Faculty of Medicine Universitas Padjadjaran, 2023)
Background: Hypertension is the most common comorbid disease which can cause further complications in COVID-19 patients. On the contrary, the pandemic has also caused lower health services and adherence to hypertension therapy. This study aimed to examine the impact of the COVID-19 pandemic on medication adherence in people with hypertension in Indonesia.Methods: The research was conducted using an analytical quantitative method. Patients with hypertension from seven islands across Indonesia were recruited based on eligibility criteria during Bulan Bakti 2021, a social outreach by Ikatan Senat Mahasiswa Kedokteran Indonesia about basic health across Indonesia. The demographic and medication history of the respondents were recorded. The Indonesian version of the Morisky Medication Adherence Scale (MMAS-8) questionnaire was distributed, and the medication adherence level was assessed.Results: A total of 1155 patients, mainly females (62.2%) participated in this study. More than half of the patients had low adherence (55.25%). Males (Adjusted Odd Ratio (AOR) 0.777 [CI 95% 0.529–1.019]), employed (AOR 0.857 [CI 95% 0.495–1.483]), higher income (AOR 0.522 [CI 95% 0.393–0.713]), and those who had information from healthcare worker (AOR 0.583 [CI 95% 0.361–0.878]) were found to have better medication adherence in multivariate logistic regression test.Conclusion: Medication adherence level in patients with hypertension during the pandemic is markedly low. Integrated preventive and promotive measures, especially from healthcare workers, are needed to prevent further morbidity and mortality.